Polylactide-Based Materials: Synthesis and Biomedical Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on PLA-based materials and the modification of their properties for biomedical applications. Special emphasis is placed on the supramolecular strategies that lead to unique structures in the micro- or nanoscale. The development and testing of novel biomaterials as drug delivery carriers, implants, or tissue engineering scaffolds are of particular interest. Special attention is given to understanding the structure–properties relationship, since this allows for the development of the most effective biocompatible materials.